PROFIL KARAKTER INTEGRITAS DITINJAU DARI KECERDASAN INTRAPERSONAL SISWA SD KELAS 3 DALAM MENYELESAIKAN MASALAH MATEMATIKA - Wahyu Susiloningsih (Jurnal Pendidikan Dasar, 2021)
The purpose of this article is to describe the integrity character of grade 3 elementary school students in terms of intrapersonal intelligence. The value of the character of a student's integrity can be seen from being steadfast and reflected in obeying the rules as if, wearing uniforms, planning tasks on time. Meanwhile, intrapersonal intelligence is related to internal aspects in a person, such as feelings of life, emotional range, the ability to distinguish emotions, mark them, and use them to understand and guide one's own behavior. This type of research is a qualitative descriptive study. The technique of collecting data by in-depth interviews with each of these students is to determine the integrity character that they show and in triangulation with observations to determine the validity of the integrity character values ​​of these students. The test results on students who have intrapersonal intelligence are in line with the results of the integrity character values ​​which are observed that the integrity character values ​​taken by students in intrapersonal intelligence show less good results such as not using uniforms when the web meeting does not collect assignments on time. So it can be concluded that students who have intrapersonal intelligence show low integrity character values.